Fractionating the unitary notion of dissociation: disembodied but not embodied dissociative experiences are associated with exocentric perspective-taking - Braithwaite, Jason; James, Kelly; Dewe, Hayley; Medford, Nick; Takahashi, Chie; Kessler, Klaus (Frontiers in Human Neuroscience, 2013)
It has been argued that hallucinations which appear to involve shifts in egocentric perspective (i.e., the out-of-body experience: OBE) reflect specific biases in exocentric perspective-taking processes. Via a newly devised perspective-taking task, we examined whether such biases in perspective-taking were present in relation to specific dissociative anomalous body experiences – namely the OBE. Participants also completed the Cambridge Depersonalization Scale (CDS, Sierra & Berrios, 2000) which provided measures of additional embodied anomalous-bodily experiences (unreality of self) and measures of derealization (unreality of surroundings). There were no reliable differences in the level of anomalous bodily experiences, emotional numbing, and anomalies in sensory recall reported between the OBE and control group as measured by the corresponding CDS subscales. In contrast, the OBE group did provide significantly elevated measures of derealization (“alienation from surroundings” CDS subscale) relative to the control group. At the same time we also found that the OBE group was significantly more efficient at completing all aspects of the perspective-taking task relative to controls. Collectively, the current findings support fractionating the typically unitary notion of dissociation by proposing a distinction between embodied dissociative experiences and disembodied dissociative experiences - with only the latter being associated with exocentric perspective-taking mechanisms. Our findings - obtained with an ecologically valid task and a homogeneous OBE group - also call for a re-evaluation of the relationship between OBE and perspective taking in terms of facilitated disembodied experiences.